Analisa Peramalan Penjualan Alat Kesehatan dan Laboratorium di PT. Tristania Global Indonesia Menggunakan Metode ARIMA - Lafnidita Farosanti (J I M P - Jurnal Informatika Merdeka Pasuruan, 2022)
Forecasting (forecasting) product sales in the business world provides significant benefits. A company can predict the number of sales in the future based on past data. PT Tristania Global Indonesia is a company that supplies customer requests in the form of medical and laboratory equipment in the Bali area and its surroundings. Transaction data owned by PT TGI has not been used optimally and is only a historical record so that further processing is needed. Through the transaction data, product sales forecasting analysis will be carried out using the Auto Regressive Integrated Moving Average (ARIMA) method with parameters p,d,q of 4,2,1. This parameter test was implemented on one of the categories of goods and city names, namely "Microbiology" and "Denpasar" for a total of 1872 data. Evaluation of the method using the Root Mean Square Error (RMSE) formula produces a value of 4.129 (0.04129). This shows that the product sales forecasting analysis using the ARIMA method has an acceptable error value, which is less than one of the critical values or alpha of 0.05, so this forecasting method is suitable to be applied to cases at PT. TGI.Keywords— Forecasting, Autoregressive, Moving Average